Efektivitas Pembinaan Karakter Peserta Didik di Masa Pandemi Covid-19 (Studi Kasus di MTs Terpadu Labbaik Lahat) - Nugraha, Ariq Naufal; Fitria, Happy; Mulyadi, Mulyadi (Program Studi Manajemen Pendidikan Islam Fak. Ilmu Tarbiyah dan Keguruan, 2023)
This study aims to determine the effectiveness of character building during a Covid 19 pandemic at MTs Terpadu Labbaik Lahat. The focus of this study is to determine the effectiveness of personality building, especially in terms of religious personality and student disciplined personality. This study uses a descriptive qualitative approach. The subjects / informants of this survey are the head master of Madrasah, the deputy head of the madrasah, teachers, and student representatives. Method Data collection are performed using four types of methods: observation, interview, and documentation. The data analysis techniques used are data reduction, data display, and drawing inference. From the results of the data analysis, the following results were obtained. How to coach in MTs. Terpadu Labbaik runs through the implementation of the building the character program. This program includes leadership, entrepreneurship, Friday shows and familiarity, or Murajah programs. This program has helped change the character of students, such as Al-Matsurat's independent reading, disciplined prayer, and increased self-confidence in public.